GENETIC ANALYSIS COVERING LOAMS OF STAVROPOL - Boris Fedorovich Galay; Vitaliy Victorovich Serbin; Victoria Sergeevna Plakhtyukova; Oleg Borisovich Galay (Наука. Инновации. Технологии)
In the territory of Stavropol, integumentary loams have broad, almost universal distribution and lie on various elements of a relief. Article is devoted to questions of wrong opinion of local geologists and authoritative scientists of Russia, which carry this soil to diluvial educations. Based on new achievements of paleogeography and paleoclimatology proved the Genesis of Aeolian loams and their belonging to single loess formations in the South of Russia. Questions, extremely important for an explanation of genesis of integumentary loams are considered: what geological agent how, from where and, the main thing, under what physiographic conditions primary material for integumentary loams of Stavropol could deliver? The geological section of districts of Stavropol from the prospecting reports showing against diluvial genesis of integumentary loams of the city. Analyzed assessment of the Genesis of covering loams as the following extracts from reports and of the city, planning regulations and the findings based paleogeographic environment of their accumulation.